2016
DOI: 10.1016/j.neulet.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic changes following traumatic brain injury and their implications for outcome, recovery and therapy

Abstract: Traumatic brain injury (TBI) contributes to nearly a third of all injury-related deaths in the United States. For survivors of TBI, depending on severity, patients can be left with devastating neurological disabilities that include impaired cognition or memory, movement, sensation, or emotional function. Despite the efforts to identify novel therapeutics, the only strategy to combat TBI is risk reduction (helmets, seatbelts, removal of fall hazards, etc.). Enormous heterogeneity exists within TBI, and it depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 110 publications
0
55
0
Order By: Relevance
“…The genomic response to injury is an important area of current research. Recent studies have revealed that traumatic injuries result in epigenetic changes via DNA methylation, phosphorylation, and acetylation (Wong & Langley, 2016). The so-called "genomic storm" following injury occurs on an epigenetic level and modulates numerous cellular functions, protein expression, and pathways.…”
Section: Tbi Creates a Genomic Stormmentioning
confidence: 99%
“…The genomic response to injury is an important area of current research. Recent studies have revealed that traumatic injuries result in epigenetic changes via DNA methylation, phosphorylation, and acetylation (Wong & Langley, 2016). The so-called "genomic storm" following injury occurs on an epigenetic level and modulates numerous cellular functions, protein expression, and pathways.…”
Section: Tbi Creates a Genomic Stormmentioning
confidence: 99%
“…These changes are collectively referred to as “epigenetics” and involve modulation of gene expression and phenotype while maintaining the underlying DNA sequence. Of note, these epigenetic changes following TBI have also been implicated in recovery from TBI as well . Therefore, modulation of these pathways can may play a potential role in treatment of TBI.…”
Section: Tbi Triggers a Genomic And Proteomic Stormmentioning
confidence: 99%
“…Overall, these studies have shown a potential role of miRNA as TBI biomarkers, but only miR21 has been identified as a candidate in more than one study [198,199]. Given that pre-clinical optimism in finding good biomarkers in the past has not been successfully translated in clinical settings [200], further evaluation of these miRNAs with larger, multicenter patient cohorts is needed to explore their use as effective biomarkers applied to diagnosis and prognosis of TBI.…”
Section: Micrornasmentioning
confidence: 99%